1989
DOI: 10.1055/s-2007-1009170
|View full text |Cite
|
Sign up to set email alerts
|

Triac Reduces Serum TSH Without Decreasing Alpha and Beta TSH Messenger RNAS

Abstract: Triac, 3,5,3'-triiodothyroacetic acid, was administered at doses of 1, 3, 9 or 30 micrograms/100 g body weight to hypothyroid rats to determine its effects on TSH secretion and pituitary mRNA content. Triac caused a dose-dependent decrease in serum TSH 6 h after injection. Pituitary content of mRNA subunits either remained at hypothyroid levels or increased at 6 h. At 24 h after injection of the 3 micrograms dose of triac, serum TSH returned to hypothyroid levels; both alpha and beta mRNA subunits were reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…From these and other studies it was estimated that 62 µg (100 nmol)/kg/day TA3 has an equal TSH-suppressive effect as 16 µg (20 nmol)/kg/day LT 4 . Interestingly, Mirell and coworkers (Mirell et al 1989) found that TSH mRNA expression levels are unchanged 6 h after TA 3 administration, suggesting that the initial decline in serum TSH is not caused by alterations at transcriptional level, but rather points to direct inhibition of TSH secretion by TA 3 . In contrast, prolonged (>12 days) TA 3 administration to rats persistently suppressed pituitary TSH mRNA levels (Juge-Aubry et al 1995, Liang et al 1997, resulting in a dose-dependent decrease in serum T 3 and T 4 levels (Medina-Gomez et al 2008).…”
Section: Effects Of Ta 3 On the Hypothalamuspituitary-thyroid (Hpt) Axismentioning
confidence: 99%
“…From these and other studies it was estimated that 62 µg (100 nmol)/kg/day TA3 has an equal TSH-suppressive effect as 16 µg (20 nmol)/kg/day LT 4 . Interestingly, Mirell and coworkers (Mirell et al 1989) found that TSH mRNA expression levels are unchanged 6 h after TA 3 administration, suggesting that the initial decline in serum TSH is not caused by alterations at transcriptional level, but rather points to direct inhibition of TSH secretion by TA 3 . In contrast, prolonged (>12 days) TA 3 administration to rats persistently suppressed pituitary TSH mRNA levels (Juge-Aubry et al 1995, Liang et al 1997, resulting in a dose-dependent decrease in serum T 3 and T 4 levels (Medina-Gomez et al 2008).…”
Section: Effects Of Ta 3 On the Hypothalamuspituitary-thyroid (Hpt) Axismentioning
confidence: 99%
“…These results would indicate that although TSH is an important factor in thyroid cell proliferation, other TSH-independent signaling mechanisms may be of major importance to growth regulation of the thyroid gland [39]. It should be noted that other authors have previously demonstrated a prolonged effect on TSH inhibition after 30 g of TRIAC or 1 g of T 3 administered in a single daily dose [40].…”
Section: Discussionmentioning
confidence: 66%